Ministry Of Finance Decree No. 20 For The Year 2023 On Amending Certain Provisions Of The Executive Regulations Of The Uniform Tax Procedure Law, Issued By Minister Of Finance Decree No. 286 Of The Year 2021 = وزارة المالية قرار رقم 20 لسنة 2023 بتعديل بعض أحكام اللائحة التنفيذية لقانون الإجراءات الضريبية الموحد الصادرة بقرار وزير المالية رقم 286 لسنة 2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic